NOS2-derived low levels of NO drive psoriasis pathogenesis - Ines Köhler; Cecilia Bivik Eding; Nada-Katarina Kasic; Deepti Verma; Charlotta Enerbäck (Cell Death and Disease, 2024)
Abstract Psoriasis is an IL-23/Th17-mediated skin disorder with a strong genetic predisposition. The impact of its susceptibility gene nitric oxide synthase 2 (NOS2) remains unknown. Here, we demonstrate strong NOS2 mRNA expression in psoriatic epidermis, an effect that is IL-17 dependent. However, its complete translation to protein is prevented by the IL-17-induced miR-31 implying marginally upregulated NO levels in psoriatic skin. We demonstrate that lower levels of NO, as opposed to higher levels, increase keratinocyte proliferation and mediate IL-17 downstream effects. We hypothesized that the psoriatic phenotype may be alleviated by either eliminating or increasing cellular NO levels. In fact, using the imiquimod psoriasis mouse model, we found a profound impact on the psoriatic inflammation in both IMQ-treated NOS2 KO mice and wild-type mice treated with IMQ and the NO-releasing berdazimer gel. In conclusion, we demonstrate that IL-17 induces NOS2 and fine-tunes its translation towards a window of proinflammatory and hyperproliferative effects and identify NO donor therapy as a new treatment modality for psoriasis.